An Integrated Design Study for an Advanced Tokamak to Close Physics Gaps in Energy Confinement and Power Exhaust. (3rd April 2023) - Weisberg, D. B.; Leuer, J.; McClenaghan, J.; Yu, J. H.; Wehner, W.; McLaughlin, K.; Abrams, T.; Barr, J.; Grierson, B.; Lyons, B.; MacDonald, J. R.; Meneghini, O.; et al.
Abstract: A high-level design study for a new experimental tokamak shows that advances in fusion science and engineering can be leveraged to narrow the gaps in energy confinement and exhaust power handling that remain between present devices and a future fusion pilot plant (FPP). This potential new U.S. facility, an Exhaust and Confinement Integration Tokamak Experiment (EXCITE), will access an operational space close to the projected FPP performance regime via a compact, high-field, high-power-density approach that utilizes advanced tokamak scenarios and high-temperature superconductor magnets. Full-device optimization via system code calculations, physics-based core-edge modeling, plasma control simulations, and finite element structural and thermal analysis has converged on a B T = 6  T, I P = 5  MA, R 0 = 1.5  m, A = 3, D-D tokamak with strong plasma shaping, long-legged divertors, and 50 MW of auxiliary power. Such a device will match several absolute FPP parameters: plasma pressure, exhaust heat flux, and toroidal magnetic field. It will also narrow or close the gap in key dimensionless parameters: toroidal beta, bootstrap fraction, collisionality, and edge neutral opacity. Integrated neutron shielding preserves personnel access by limiting nuclear activation and maximizes experimental run time by reducing site radiation. In addition to design study results and optimization details, parameter sensitivities and uncertainties are also discussed.